Relationship between Team Satisfaction and Project Performance as Perceived by Project Managers in Malaysia – A Mixed Methods Study - Siow, Heng Loke; Fung, Han Ping (Sciknow Publications Ltd., 2013)
The purpose of this mixed methods sequential explanatory study was to evaluate what are the team outcome factor(s) that can contribute to project performance in Malaysia by surveying 52 project managers. Later, the study continued by following up with six selected participants to investigate those positive results in more detail via an online interview. In the first phase, only one team outcome factor i.e. team satisfaction was tested significantly influencing project performance. In the second phase, multiple case studies were conducted to investigate how and why team satisfaction influences project performance whereby four major themes emerged from the “how” question and one major theme emerged from the “why” question. The findings of both phases were discussed. Limitations and future recommendation were also provided.